WARRANTY MAINTENANCE OF TECHNICALLY COMPLEX EQUIPMENT IN THE ECONOMIC SPHERE (LEGAL ASPECT) - Milimko, Larysa (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2021)
Purpose: to characterize the legal regulation of warranty service of technically complex equipment in the economic sphere; identify problems and make suggestions for improving legal regulation in this area. Methods: the study was conducted using such methods as analysis, synthesis, comparison. Results: in the article the author gives a description of the legal regulation of relations for warranty service of technically complex equipment in the economic sphere. For the first time the author’s definition of the concept of «technically complex equipment» is formulated, that it is non-consumable things belonging to things of technical purpose which have long service life and maintenance of which quality in the course of operation demands qualified, professional service. It is established that at the current stage of legal regulation the terms and concepts of warranty service of technically complex equipment are characterized by a lack of clear definition and diversity and therefore there is a need in economic legislation to bring them to universal. The correlations of the concepts «technically complex equipment», «products of industrial and technical purpose» are substantiated and it is established that technically complex equipment belongs to products of industrial and technical purpose. The author outlines some aspects of supply contracts and others that contain provisions for warranty service of technically complex equipment and found that in practice in commercial contracts (including - in public procurement contracts) for warranty and post-warranty service, the parties, as a rule, the provisions reflected in the «Procedure for warranty repair (maintenance) or warranty replacement of technically complex household goods» are indicated, Although business entities cannot officially refer to the norms and provisions of this normative legal act, as it clearly states that this Procedure defines the relations with the participation of consumers who purchase technically complex household goods for their own household needs. The analysis of court practice on resolving disputes in the field of warranty service of technically complex equipment was also carried out and it was established that the main part of litigation is compensation for damages arising from improper performance of warranty service agreements. Proposed, in accordance with the provisions of Art. 271 of the Civil Code of Ukraine, it is advisable to regulate the supply of certain types of goods (in particular, products for industrial and technical purposes, consisting of technically complex equipment) with special conditions for the supply of certain types of goods, approved by Cabinet of Ministers of Ukraine. Discussion: problems of legal regulation of warranty service of technically complex equipment in the economic sphere.